Microbial biosynthesis and in vivo depolymerization of intracellular medium‐chain‐length poly‐3‐hydroxyalkanoates as potential route to platform chemicals - Anis, Siti Nor Syairah; Annuar, Mohamad Suffian Mohamad; Simarani, Khanom (Wiley, 2018)
Biosynthesis and in vivo depolymerization of intracellular medium-chain-length poly-3-hydroxyalkanoates (mcl-PHA) in Pseudomonas putida Bet001 grown on lauric acid were studied. Highest mcl-PHA fraction (>50 % of total biomass) and cell concentration (8 g L −1 ) were obtained at carbon-to-nitrogen (C/N) ratio 20, starting cell concentration 1gL −1 , and 48 H fermentation. The mcl-PHA comprised of 3-hydroxyhexanoate (C 6 ), 3-hydroxyoctanote (C 8 ), 3-hydroxydecanoate (C 10 ), and 3-hydroxydodecanoate (C 12 ) monomers. In vivo action was studied in a mineral liquid medium without carbon source, and in different buffer solutions with varied pH, molarity, ionic strength, and temperature. The monomer liberation rate reflected the molpercentage distribution of the initial polymer subunit composition. Rate and percentage of in vivo depolymerization were highest in 0.2 M Tris–HCl buffer (pH 9, strength = 0.2 M, 30°C) at 0.21 g L −1 H −1 and 98.6 ± 1.3 wt%, respectively. There is a congruity vis-à-vis to specific buffer type, molarity, pH, ionic strength, and temperature values for superior in vivo depolymerization activities. Direct products from in vivo depolymerization matched the individual monomeric composition of native mcl-PHA. It points to exo-type reaction for the in vivo process, and potential biological route to chiral molecules.